Peluang dan Tantangan Desa Wisata Kebun Tinggi Kabupaten Kampar Provinsi Riau Sebagai Destinasi Wisata Berkelanjutan - Rahmad Ramadan; Nur Widiyanto; John Joi Ihalauw (CV. Ulil Albab Corp, 2022)
This study aims to find out how the opportunities and challenges faced by Kebun Tinggi Tourism Village, Kampar Regency, Riau Province as a sustainable tourism destination and how to implement the concept of sustainable tourism and how the role of stakeholders in carrying out development in Kebun Tinggi Village, Kampar Regency, Riau Province.This research is a qualitative descriptive type. Data collection techniques were obtained in the form of observation, documentation and interviews, then data processing and analysis were carried out to obtain an overview of the variables involved in the study.The results of the study explain that the opportunities possessed by Kebun Tinggi Tourism Village are that the area still has a lot of tourism potential that can be developed further and the biggest challenges are the lack of infrastructure and the absence of telephone or internet networks. The feasibility of the Kebun Tinggi Tourism Village, Kampar Regency, Riau Province as a sustainable destination can be seen from the cultural preservation activities in the community that are still maintained and the presence of these tours has proven to have an impact on increasing living standards in the community and with the existence of tourist destinations in the tourist area, although many forest areas are still intact. asri has been converted, but is still carried out within reasonable limits. Each stakeholder involved in the development of the Kebun Tinggi Tourism Village has carried out its role in accordance with the functions of each stakeholder.